Meningkatkan Kepuasan Kerja Pegawai Melalui Kedisiplinan Dan Pelatihan: Studi Empiris Pada Tenaga Kependidikan Universitas Islam Negeri Antasari Banjarmasin - M Meliani; Misransyah Akos (Administraus, 2020)
This study aims: (1) to know, test and analyze the influence of work discipline on the job satisfaction of UIN Antasari Banjarmasin Education Personnel; 2) to find out, test and analyze the effect of training on the job satisfaction of UIN Antasari Banjarmasin Education Personnel. The study uses descriptive quantitative methods. The population of the study was Civil Servants (PNS) Education Personnel UIN Antasari Banjarmasin, totaling 111 (one hundred and eleven people). The sample is 63 people. The independent variable is work discipline and training while the dependent variable is job satisfaction. Data collection is done by distributing questionnaires. Data analysis using partial (Partial Least Square / PLS) regression analysis. The results of this study indicate (1) that work discipline has a positive and significant effect on job satisfaction of 0,000. (2) that training has a positive but not significant effect on job satisfaction of 0.416. Conclusion: Work discipline has a positive and significant effect on job satisfaction of UIN Antasari Banjarmasin employees. Training has a positive but not significant effect on job satisfaction of UIN Antasari Banjarmasin employees. Suggestion: leaders must be more assertive and pay attention to the work discipline of UIN Antasari Banjarmasin employees to improve job satisfaction so that employees can work better effectively and efficiently